Kemampuan Pemahaman Konsep Matematika Siswa Melalui Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) pada Pembelajaran Matematika di Kelas VIII SMP PGRI 1 Betung - Muhammad Yogi Ramadhan; Eka Yanuarti (Institut Agama Islam Negeri Curup, 2020)
This study aims to determine the ability of students to understand mathematical concepts through the Indonesian Realistic Mathematics Education (PMRI) approach to learning mathematics in class VIII of SMP PGRI 1 Betung. This research is a